AB0768 BASELINE PAIN SEVERITY AS A PREDICTOR OF PAIN IMPROVEMENT FOLLOWING TREATMENT WITH TOFACITINIB IN PSORIATIC ARTHRITIS. (June 2019) - Ogdie, Alexis; Vlam, Kurt de; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Mease, Philip J.; Fleischmann, Roy; Taylor, Peter C.; Azevedo, Valderilio F.; Fallon, Lara; Maniccia, Anna; Woolcott, John
Abstract : Background: Pain is a core domain of psoriatic arthritis (PsA). 1 Rapid, sustained pain reduction is a priority for patients (pts) and physicians when choosing treatment. Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. Objectives: This post hoc analysis aimed to estimate time to clinically meaningful pain improvement with tofacitinib. Methods: Data were analysed from 2 Phase 3 studies of tofacitinib in pts with active PsA and an inadequate response to ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD) (OPAL Broaden; NCT01877668 ; 12-month study), or to ≥1 tumour necrosis factor inhibitor (OPAL Beyond; NCT01882439 ; 6-month study). Pts treated with tofacitinib 5 mg twice daily (BID) and placebo (PBO) advanced to tofacitinib 5 mg BID at Month 3 (PBO-tofacitinib), in combination with csDMARDs, were included in this analysis. Current arthritis pain severity was reported by pts using a 100 mm visual analogue scale, where higher scores indicated greater severity of pain. Pain improvement was defined as the first post-baseline improvement of ≥30% (meaningful change), ≥50% (substantial change) or ≥70% relative to baseline. 2 Time-to-event analyses were performed using a Kaplan-Meier (KM) method on pooled data. Descriptive analyses of the rate of improvements by study were performed. Results: Overall, 354 pts were available for analysis. Rates of pain improvement over time with tofacitinib 5 mg BID were approximately the same in both studies (Figure). By Month 1, ≥40% of pts experienced ≥30% pain improvement, and by Month 2, approximately 55% of pts experienced ≥30% pain improvement (Figure). KM analyses showed that pts receiving tofacitinib 5 mg BID achieved improvements in pain severity of 30–70% significantly faster compared with pts in the PBO-tofacitinib group (Table). The median time to ≥30% pain improvement was 55 days in the tofacitinib 5 mg BID group and 106 days in the PBO-tofacitinib group (pts switched to tofacitinib 5 mg BID at Month 3; p=0.0132). Similar trends between treatment groups were observed across other pain improvement thresholds. Conclusion: In pts with active PsA, faster, clinically meaningful pain improvements were reported in pts receiving tofacitinib 5 mg BID vs pts receiving PBO who switched to tofacitinib 5 mg BID at Month 3. After switch from PBO to active treatment, pain improvement was observed in line with pts receiving active treatment from Day 0. To achieve pain improvement at greater thresholds, longer duration of active treatment was required. References: [1] Orbai aM, et al. Ann Rheum Dis2017;76:673-80. [2] Dworkin RH, et al. J Pain2008;9:105-21. Acknowledgement: This study was sponsored by Pfizer inc. Medical writing support was provided by Karleen Nicholson, PhD, on behalf of CMC Connect, a division of McCann Health Medical Communications Ltd, Macclesfield, UK, and was funded by Pfizer inc. Disclosure of interests: Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: abbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: abbVie, amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer inc, Takeda, Consultant for: abbvie, amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: abbvie, amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Kurt de Vlam Consultant for: Pfizer inc, Consultant for: Johnson & Johnson, andrew G Bushmakin Shareholder of: Pfizer inc, Employee of: Pfizer inc, Joseph C Cappelleri Shareholder of: Pfizer inc, Employee of: Pfizer inc, Philip J Mease Grant/research support from: abbVie, amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: abbVie, amgen, BMS, Galapagos, Gilead Sciences, inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: abbVie, amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Roy Fleischmann Grant/research support from: abbVie, amgen, astraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer inc, Sanofi-Aventis, UCB, Consultant for: abbVie, amgen, astraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer inc, Sanofi-Aventis, UCB, Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: abbVie, Galapagos, Gilead, Eli Lilly, Pfizer inc, Valderilio F azevedo Grant/research support from: abbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer inc, UCB, Consultant for: abbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer inc, UCB, Lara Fallon Shareholder of: Pfizer inc, Employee of: Pfizer inc, anna Maniccia Shareholder of: Pfizer inc, Employee of: Pfizer inc, John Woolcott Shareholder of: Pfizer inc, Employee of: Pfizer inc